Advanced 3D Geophysical Imaging Technologies for Geothermal Resource Characterization - Zhang, Haijiang; Gasperikova, Erika; Parker, Beatrice; Tryggvason, Ari; Gudmundsson, Olafur; Seher, Tim; Newman, Gregory; Fehler, Michael; Arnason, Knutur (Massachusetts Institute of Technology. Earth Resources Laboratory, 2012)
We describe the ongoing development of joint geophysical imaging methodologies for geothermal site characterization and demonstrate their potential in two regions: Krafla volcano and associated geothermal fields in Northeastern Iceland, and Coso Hot Springs in California, USA. The Coso field is a high temperature reservoir similar to Krafla in Iceland. Each area is a locus of significant geothermal energy production. The complex geology of these sites also makes them excellent targets for developing and testing of strategies for joint imaging of magnetotelluric (MT) and micro-earthquake (MEQ) data. Our ultimate aim is to construct coupled 3D resistivity and velocity models of these geothermal systems and use them to better understand and exploit them. Lawrence Berkeley National Laboratory (Subcontract 6927716)